Quantum Mechanics Insight into the Microwave Nucleation of SrTiO3 Nanospheres - Moreira, Mario L.; Longo, Valeria M. [UNESP]; Avansi, Waldir [UNESP]; Ferrer, Mateus M.; Andres, Juan; Mastelaro, Valmor R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Amer Chemical Soc, 2012)
An extensive investigation of strontium titanate, SrTiO3 (STO), nanospheres synthesized via a microwave-assisted hydrothermal (MAH) method has been conducted to gain a better insight into thermodynamic, kinetic, and reaction phenomena involved in STO nucleation and crystal growth processes. To this end, quantum chemical modeling based on the density functional theory and periodic super cell models were done. Several experimental techniques were employed to get a deep characterization of structural and optical features of STO nanospheres. A possible formation mechanism was proposed, based on dehydration of titanium and strontium clusters followed by mesoscale transformation and a self-assembly process along an oriented attachment mechanism resulting in spherical like shape. Raman and XANES analysis renders a noncentrosymmetric environment for the octahedral titanium, while infrared and first order Raman modes reveal OH groups which are unsystematically incorporated into uncoordinated superficial sites. These results seem to indicate that the key component is the presence of distorted TiO6 clusters to engender a luminescence property. Analysis of band structure, density of states, and charge map shows that there is a close relationship among local broken symmetry, polarization, and energy split of the 3d orbitals of titanium. The interplay among these electronic and structural features provides necessary conditions to evaluate its luminescent properties under two energy excitation.